2023
DOI: 10.36227/techrxiv.22223191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abduction/Adduction Assistance from Powered Hip Exoskeleton Enables Modulation of User Step Width During Walking

Abstract: <p>Abstract-Using wearable robotics to modulate step width in  normal walking for enhanced mediolateral balance has not been  demonstrated in the field. We designed a bilateral hip exoskeleton  with admittance control to power hip abduction and adduction to  modulate step width. Objective: As the first step to show its potential, the objective of  this study was to investigate how human’s step width reacted to  hip exoskeleton’s admittance control parameter changes during  walking.  </p> <p>M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The input moments of the mechanism are generated by using a closed-loop admittance control strategy [8], [23]. This strategy takes into account the compliance of the flexible shaft used to transmit power from the motor to the test bench.…”
Section: ) Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The input moments of the mechanism are generated by using a closed-loop admittance control strategy [8], [23]. This strategy takes into account the compliance of the flexible shaft used to transmit power from the motor to the test bench.…”
Section: ) Controllermentioning
confidence: 99%
“…Biomechanical simulations have suggested that muscles involved in hip abduction (outward rotation on the frontal plane) are the most effective for reducing metabolism [6]. It has been proposed that an exoskeleton that assists the frontal plane can control the step width, improving walking stability [7], [8]. Thus, within the context of the three-dimensional moments governing walking, both the sagittal plane moment contributing to forward propulsion and the frontal plane moment contributing to stability are essential.…”
mentioning
confidence: 99%
“…While previous research has predominantly focused on anterior-posterior gait parameters such as stride length and walking speed, limited attention has been given to mediolateral measurement, particularly stride width [3], [4]. However, stride width, associated with foot placement strategy and influencing the interaction between the body's center of mass and base of support [5]- [7], plays a crucial role in gait stability, postural balance control, and fall risk reduction for both healthy subjects and individuals with neurodegenerative disease [8]- [11]. Through active adjustment of stride width, individuals optimize energy efficiency [6], enhance dynamic margins of stability [12], negotiate small obstacles [13], and overcome external disturbances during walking [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stride width is also linked to gait compensatory mechanisms and serves as a modifiable factor in effective fall prevention training [8], [19]. Individuals with neurodegenerative disease, especially those with cerebellar ataxia, often exhibit a wider stride width to mitigate fall risks, counteract trunk instability, and enhance adaptability [19]- [22].…”
Section: Introductionmentioning
confidence: 99%